Constraints Perceived by the Tribal and Non-Tribal Farmers in CorianderProduction Technology in Jhalawar, Rajasthan - Meena, D. K.; Bareth, L. S.; Badhala, B. S.; Lal, Hanuman (Indian Journal of Extension Education, 2011)
Coriander is an important dominant and highly valued spice grown in India. It is the first probably the first spices to be used by men as common flavouring substance. The stem leaves and grains have a pleasant aroma. The entire plant used in preparing “Chatany” whereas, leaves are used for flavouring curries, sauce and soups. The dry grains are extensively used in preparation of curry powder, pickling spices and seasoning. This study was conducted in Khanpur Panchayat Samiti of Jhalawar district, which was selected purposely. Among the four constraints, constraints related to miscellaneous was the major constraints perceived by the coriander growers. This constraint was followed by constraints related to input, marketing. Least perceived constraints were technical constraints. The overall constraints faced by the tribal respondents were 56.78 MPS. Whereas in case of non-tribal respondents it was 49.58 MPS. There were rank order correlations in all aspects of constraints between tribal and non-tribal coriander growers.